Measuring Women's Agency - Donald, Aletheia; Koolwal, Gayatri; Annan, Jeannie; Falb, Kathryn; Goldstein, Markus (World Bank, Washington, DC, 2017)
Improving women's agency, namely their ability to define goals and act on them, is crucial for advancing gender equality and the empowerment of women. Yet, existing frameworks for women's agency measurement -- both disorganized and partial -- provide a fragmented understanding of the constraints women face in exercising their agency, restricting the design of quality interventions and evaluation of their impact. This paper proposes a multidisciplinary framework containing the three critical dimensions of agency: goal-setting, perceived control and ability ("sense of agency"), and acting on goals. For each dimension, the paper (i) reviews existing measurement approaches and what is known about their relative quality; (ii) presents new empirical evidence from Sub-Saharan Africa: validating vignettes as a measurement tool for goal-setting, examining gender and regional discrepancies in response to sense-of-agency measures, and investigating what information spousal disagreement over decision-making roles can provide about the intra-household process of acting on goals; and (iii) highlights priorities for future research to improve the measurement of women’s agency.